2015
DOI: 10.1007/s13277-015-3982-1
|View full text |Cite
|
Sign up to set email alerts
|

PRSS1 mutations and the proteinase/antiproteinase imbalance in the pathogenesis of pancreatic cancer

Abstract: This study aimed to investigate the mutations in the serine protease 1 gene (PRSS1) and the imbalance between trypsin and α1-antitrypsin in patients with pancreatic cancer. Polymerase chain reaction (PCR) was performed to amplify the sequences of PRSS1 from 65 patients with pancreatic cancer and 260 healthy controls, direct sequencing was performed, and the clinical features were analyzed. In addition, enzyme-linked immunosorbent assay (ELISA) was employed to detect serum trypsin and α1-antitrypsin in pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
4
9
0
Order By: Relevance
“…The results revealed that multiple loci contained one of three genotypes: C/C, C/T or T/T (Fig. 1), which is similar to results that have been previously reported (18,19). Moreover, 58 patients with PDAC (43.75%) had the T/C genotype (Table I), which was regarded as a mutation.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results revealed that multiple loci contained one of three genotypes: C/C, C/T or T/T (Fig. 1), which is similar to results that have been previously reported (18,19). Moreover, 58 patients with PDAC (43.75%) had the T/C genotype (Table I), which was regarded as a mutation.…”
Section: Resultssupporting
confidence: 90%
“…PRSS1 encodes trypsin-1, the main trypsinogen enzyme secreted by the pancreas. PRSS1 mutations have been associated with increased trypsin-1 serum levels as well as the trypsin and α1-antitrypsin imbalance observed in patients with pancreatic cancer, which may alter the pancreatic microenvironment and increase immunological escape and clonal proliferation of pancreatic cancer cells (19). However, the clinicopathological and prognostic significance of PRSS1 mutations in patients with PDAC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The R117H mutation is a frequently observed germline mutation in PRSS1. N29I, A16V, D22G, K23R, A121T, and R122C mutations in the PRSS1 gene have also been reported to be rare mutations in cationic trypsinogen [39][40][41][42][43]. Among these mutations, we recurrently observed the A16V(C→T) mutation in 40% (8/20) of secretory carcinoma cases.…”
Section: Discussionmentioning
confidence: 69%
“…31 Although the risk for pancreatic cancer may be lower than previously thought, 31 it may serve as a model for the role of pathological intracellular activation of trypsin that also play a role in pancreatic cancerogenesis. [32][33][34] However, direct mutation in the gene is unlikely to be the explanation in the vast majority of patients with PDAC, although being a likely key component in the risk of families with hereditary pancreatitis. 31,35 Trypsin in pancreatic precursor and other neoplastic lesions of the pancreas Trypsin has proliferative capacity, as demonstrated in several studies.…”
Section: An Enemy Within: a Trojan Horse To Cancer Invasiveness?mentioning
confidence: 99%
“…Further, gene expression may not reveal significant differences between normal and neoplastic tissue as trypsinogen is omnipresent in pancreatic tissue and ductal epithelial cells due to the physiological function of the exocrine role of the pancreas. In 1 study of 65 patients with pancreatic cancer, 8 (12.3%) patients had mutation in the serine protease 1 gene (PRSS1) coding for the cationic trypsinogen (trypsin 1), 33 with corresponding higher serum levels of trypsin compared to nonmutated cancers and controls. In another series of patients, mutation of PRSS1 did not seem to play a role in terms of pancreatic cancer development.…”
Section: Why Has Trypsin Yet To Be Investigated As a Major Player Befmentioning
confidence: 99%